2021
DOI: 10.1016/j.ajog.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum is associated with increased rates of termination of pregnancy and suicidal ideation: results from a survey completed by >5000 participants

Abstract: Hyperemesis gravidarum (HG) has a detrimental effect on physical and mental health. Termination of pregnancy (TOP) is reported in approximately 10%, 1 and qualitative research studies report an association with suicidal ideation. 2 We aimed to determine the consequences of HG on TOP and suicidal ideation, with particular reference to disease severity, functional status, and perception of care. STUDY DESIGN:This national cross-sectional study utilized a 14-item anonymous online survey distributed across the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 2 publications
0
58
0
2
Order By: Relevance
“…Previous surveys have identified a termination rate for HG between 3% and 15%. 3 , 11 , 26 Poursharif et al 3 reported that 6% (49/808 women) underwent multiple terminations for HG and an additional 13% “almost” terminated their pregnancy due to HG. Although in our study only one woman terminated a pregnancy due to developing HG again, we found that 23% of women considered terminating a pregnancy, which is consistent with a rate of 26.7% (56/210 women) reported in a Scandinavian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous surveys have identified a termination rate for HG between 3% and 15%. 3 , 11 , 26 Poursharif et al 3 reported that 6% (49/808 women) underwent multiple terminations for HG and an additional 13% “almost” terminated their pregnancy due to HG. Although in our study only one woman terminated a pregnancy due to developing HG again, we found that 23% of women considered terminating a pregnancy, which is consistent with a rate of 26.7% (56/210 women) reported in a Scandinavian population.…”
Section: Discussionmentioning
confidence: 99%
“…reporting on the effect of HG on women's lives and is recognized by our Patient and Public Involvement representatives.Previous surveys have identified a termination rate for HG between 3% and 15% 3,11,26. Poursharif et al3 reported that 6% (49/808 Baseline characteristics of women included in this follow-up study…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Maternal complications include electrolyte disturbance (15-28%), Wernicke's encephalopathy (secondary to thiamine deficiency) (<1%), and susceptibility to thrombus 5,6 . Mental health complications include increased rates of anxiety (46%), depression (47.8%) and suicidal ideation (6.6%) [7][8][9][10][11][12][13] . Effects on the fetus include a four-fold increased risk of low birthweight and preterm birth and three-fold increased odds of neurodevelopmental delay 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey of >5000 women with HG, 40% perceived their experience in primary care to be poor or extremely poor in terms of HG management 13 . These women were more likely to terminate a wanted pregnancy as a consequence of HG or experience suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%